Estimating Vehicular Emission in Kathmandu Valley, Nepal - Ghimire, Krishna Prasad; Shrestha, Shreejan Ram (International Journal of Environment, 2014)
The study estimate, the vehicular emission load for CO, CO2 , HCs, NOX, SO2, Dioxin/Furans, Particulate Matters (PM10, PM2.5, Black carbon and Organic Carbon) by using emission factors and Global Warming Potentials (GWPs) of the pollutants (CO2, NOX, BC and OC). For this purpose, data were collected through the video tape record (in 30 sites), questionnaire survey, field visit, and literatures review. The total estimated emission of Kathmandu Valley (KV) was 7231053.12 ton/year. Of the total emission, CO2 emission was highest i.e., 91.01% followed by CO 5.03%, HC 0.96%, NOX 0.60%, PM10 0.18% and SO2 0.10%. Annually 529353.36 μg Toxic Equivalent (TEQ) of Dioxin/Furan produced and directly disperse to the ambient environment. The total estimated PM2.5, BC and OC emission were 9649.40 ton/year, 1640.4 ton/year and 2894.82 ton/year. The total carbon equivalence of the combined emissions (CO2, NOX and BC) for 100-years standard time horizon is 10579763.6 ton CO2-eq i.e., 2885390.07 ton carbon.CO2 alone will be responsible, for about 62% of the impacts for the next century from current emissions of CO2, NOX and BC. Of the total emission Heavy Duty Vehicles (HDV) emits 50%, Light Duty Vehicles (LDV) emits, 27%, 2-Wheelers emits 22% and 3-Wheeler (Tempo) emits 1%. The total emission of all pollutants combined per vehicle together was estimated to be 5.46 ton/year which was estimated as 23.63, 10.35, 1.83 and 5.58 ton/year for HDV, LDV, 2-Wheelers and 3-Wheeler respectively. DOI: http://dx.doi.org/10.3126/ije.v3i4.11742 International Journal of Environment Volume-3, Issue-4, Sep-Nov 2014 Page: 133-146